Review of Uganda’s high-risk Ebola preparedness activities enabling prompt control of imported Ebola Virus Outbreak from the Democratic Republic of Congo, June 2019 - Sandra Nabatanzi; Allan Niyonzima Muruta; Issa Makumbi; Alex Riolexus Ario; Benon Kwesiga; Atek Atwiine Kagirita; Lilian Bulage; Bernard Lubwama; Doreen Nsiimire Gonahasa; Paul Mbaka; Innocent Komakech; Maureen Nabatanzi; et al. (Journal of Interventional Epidemiology and Public Health)
Introduction: On 1 August 2018, the Democratic Republic of Congo declared its tenth Ebola Virus Disease (EVD) outbreak in North-Kivu province, 100 km from the Uganda border. Uganda immediately initiated activities to prepare for possible importation of cases. The capacity developed through these interventions was tested when three EVD cases entered Uganda through Kasese District on 10 June 2019. We describe how heightened preparedness efforts enabled prompt detection and control of the imported EVD cases within Uganda.